Darwin Koenig letter to Nicholas S. Halmi regarding bird sightings, winter 1976-1977 - Koenig, Darwinet al (1976)
Bird sightings were contributed by Darwin Koenig in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed